How do you simplify the expression (1+cosθ)(cscθ−cotθ)?
Answers
Answered by
0
Solution:
(1+cosθ)(cscθ−cotθ)
Here I am using A instead of theta.
= (1+cosA)(1/sinA - cosA/sinA)
=(1+cosA)[(1/sinA(1-cosA)]
= [(1+cosA)(1-cosA)]/(sinA)
= (1-cos²A)/sinA
= sin²A/sinA
= sinA
•••••
Answered by
0
Answer:
Step-by-step explanation:
Attachments:
![](https://hi-static.z-dn.net/files/d27/17827260a4d2f70d94d204b5495363b8.jpg)
Similar questions
Math,
7 months ago
Computer Science,
7 months ago
Sociology,
1 year ago
Math,
1 year ago
Physics,
1 year ago